Research Trends on Time Management and Workload in Nursing: A Bibliometric Analysis - Irawati Nurul Fitriyani; Lisa Musharyanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Time and workload management are crucial issues in nursing practice because they directly relate to time pressure, workflow efficiency, and nurses' psychological well-being. However, the rapid growth of publications has not been accompanied by a comprehensive scientific mapping to understand the global knowledge landscape on this topic. Mapping publication performance, distribution of country contributions, and dynamics of research themes related to time management and workload in nursing through bibliometric analysis. A bibliometric study was conducted using the Scopus database (Elsevier) covering the last 10 years. The search strategy combined keywords related to time management/time pressure/workflow management, workload/work demands/work intensity, and nursing/nurse. The initial search yielded 562 documents, which were then narrowed down to 199 publications (in the last 10 years), 173 publications (in the fields of Medicine and Nursing), and finally 164 documents (articles and reviews) for analysis. Descriptive analysis was used for annual publication trends (2016–2026) and country contributions, while keyword co-occurrence mapping, overlay maps, and density maps were performed using VOSviewer version 1.6.18. Co-occurrence mapping placed population/indexation terms (e.g., human/humans, adult, male, aged, article) as the central node, with prominent substantive themes on workload and nurse. Key clusters were identified that reflect: (1) work stress and mental health (e.g., stress/job stress, mental health/mental stress, burnout, job satisfaction), (2) management/operations and work processes (e.g., organization and management, workflow, task performance, time management/time pressure), and (3) qualitative approaches and capacity building (e.g., qualitative research, interview, content analysis, nursing education, skills, leadership). The overlay map indicates a strengthening of newer themes on time pressure, time management, procedures, and qualitative approaches, while the density map highlights hotspots on the relationship between nurse workload and stress/burnout and organizational factors. Research on time management and workload in nursing shows increasing scientific attention and is still dominated by contributions from countries with established research ecosystems. Key themes center on the relationship between nurse workload and stress/burnout, as well as organizational factors and work processes, with recent signs of increased focus on time pressure and qualitative approaches to understanding work dynamics. Future research should strengthen the standardization of workload definitions and measurements, expand geographic coverage, and evaluate organization-based interventions that can reduce workload and improve nurse well-being and service quality.